GRASP92: a package for large-scale relativistic atomic structure calculations - Parpia, F.A.; Froese Fischer, C.; Grant, I.P. (Computer physics communications, 2006)
Title of program: GRASP92 Catalogue identifier: ADCU_v1_1 Program summary URL: http://cpc.cs.qub.ac.uk/summaries/ADCU_v1_1 Program obtainable from: CPC Program Library, Queen's University of Belfast, N. Ireland Licensing provisions: no Programming language used: Fortran Computer: IBM POWERstation 320H Operating system: IBM AIX 3.2.5+ RAM: 64M words No. of lines in distributed program, including test data, etc.: 65 224 No of bytes in distributed program, including test data, etc.: 409 198 Distribution format: tar.gz Catalogue identifier of previous version: ADCU_v1_0 Journal reference of previous version: Comput. Phys. Comm. 94 (1996) 249 Does the new version supersede the previous version?: Yes Nature of problem: Prediction of atomic spectra—atomic energy levels, oscillator strengths, and radiative decay rates—using a ‘fully relativistic’ approach. Solution method: Atomic orbitals are assumed to be four-component spinor eigenstates of the angular momentum operator, j = l + s , and the parity operator Π = β π . Configuration state functions (CSFs) are linear combinations of Slater determinants of atomic orbitals, and are simultaneous eigenfunctions of the atomic electronic angular momentum operator, J, and the atomic parity operator, P. Lists of CSFs are either explicitly prescribed by the user or generated from a set of reference CSFs, a set of subshells, and rules for deriving other CSFs from these. Approximate atomic state functions (ASFs) are linear combinations of CSFs. A variational functional may be constructed by combining expressions for the energies of one or more ASFs. Average level (AL) functionals are weighted sums of energies of all possible ASFs that may be constructed from a set of CSFs; the number of ASFs is then the same as the number, n c , of CSFs. Optimal level (OL) functionals are weighted sums of energies of some subset of ASFs; the GRASP92 package is optimized for this latter class of functionals. The composition of an ASF in terms of CSFs sharing the same quantum numbers is determined using the configuration-interaction (CI) procedure that results upon varying the expansion coefficients to determine the extremum of a variational functional. Radial functions may be determined by numerically solving the multiconfiguration Dirac–Fock (MCDF) equations that result upon varying the orbital radial functions or some subset thereof so as to obtain an extremum of the variational functional. Radial wavefunctions may also be determined using a screened hydrogenic or Thomas–Fermi model, although these schemes generally provide initial estimates for MCDF self-consistent-field (SCF) calculations. Transition properties for pairs of ASFs are computed from matrix elements of multipole operators of the electromagnetic field. All matrix elements of CSFs are evaluated using the Racah algebra. Reasons for the new version: During recent studies using the general relativistic atomic structure package (GRASP92), several errors were found, some of which might have been present already in the earlier GRASP92 version (program ABJN_v1_0, Comput. Phys. Comm. 55 (1989) 425). These errors were reported and discussed by Froese Fischer, Gaigalas, and Ralchenko in a separate publication [C. Froese Fischer, G. Gaigalas, Y. Ralchenko, Comput. Phys. Comm. 175 (2006) 738–744. [7]]. This version of GRASP92 corrects these errors. Summary of revisions: (1) Correction to a logical error that affects extended optimal level (EOL) calculations important for correlation studies. Line 76 deleted from grasp92/rscf92/raw/scf.raw. Line 114 deleted from grasp92/rscf92/raw/setlag.raw. (2) The removal of a limitation on diagonal energy parameters for correlation orbitals. IF (METHOD(J).LE. 2) THEN inserted after line 84 of grasp92/rscf92/raw/solve.raw. ENDIF inserted after line 94 in grasp92/rscf92/raw/solve.raw. (3) Removal of an error in the evaluation of one-electron matrix elements for tensors of rank greater than zero. This error affected electric quadrupole (E2) transition probabilities, off-diagonal hyperfine parameters, and quadrupole moments. IF (NQ1(IA1).EQ.0.AND. NQ2(IA2).EQ.0) GOTO 100 inserted after line 179 of grasp92/lib92/raw/tnsrjj.raw. Line 194 of grasp92/lib92/raw/tnsrjj.raw replaced by IF (JBQ1(K,IJ) .NE. JBQ2(K,IJ)) GOTO 100. Restrictions: The maximum size of a multiconfiguration (MC) calculation, as measured by the length of the configuration state function (CSF) list n c , is limited by numerical stability, processing time, or storage. Numerical stability typically decreases as the number of radial functions varied increases and as the number of open subshells increases. Processing time increases as some power of n c greater than 1 but generally appreciably less than 3. Lists of angular integrals, V r s k ( a b c d ) , distinguished by tensor rank, k, are written to disk; the available disk storage must be large enough to store all such lists together. Each list is subsequently read into memory and sorted by canonically-ordered Slater integral indices a b c d ; the available memory (including any available virtual memory) must be large enough to store the longest list before it is sorted. The lengths of the unsorted and sorted lists increase as some power of n c greater than 1 but generally less than the maximum of 2. The maximum size of a configuration interaction (CI) calculation is limited by processing time and storage. Processing time increases as some power of n c greater than 1 but generally appreciably less than 2. A sparse representation of the lower triangle of the Hamiltonian matrix is written to disk; the available disk storage must be large enough to store this representation of the Hamiltonian matrix. The size of this representation of the Hamiltonian matrix increases as some power of n c greater than 1 but generally less than the maximum of 2. All orbitals that share the quantum numbers nlj (i.e., all members of a subshell) are assumed to have the same radial dependence P n l j ( r ) , Q n l j ( r ) . Orbitals with different values of the quantum numbers nlj are assumed to be orthogonal. The tables of coefficients of fractional parentage used in GRASP92 are limited to subshells with j ⩽ 7 / 2 ; occupied subshells with j = 9 / 2 are, therefore, restricted to a maximum of two electrons. Unusual features: The GRASP92 package comprises task-specific component programs for the specification of nuclear properties, the generation and manipulation of lists of configuration state functions (CSFs), the computation of radial wavefunctions, of approximate atomic state functions (ASFs), the computation of properties of electromagnetic transitions between ASFs, and for the conversion of data between machine-specific unformatted representations and universal formatted representations. All component programs in the GRASP92 package have been designed for interactive use; the number of keystrokes required by the user is reduced by the provision of defaults appropriate to the types of calculations that are expected to be performed most frequently, and by the provision of interpretation for ‘wild card’ characters as sets of data items. Several devices have been adopted to reduce computational effort and storage requirements: in multiconfiguration (MC) calculations, the list of angular integrals is presorted by tensor rank prior to sorting by canonically-ordered Slater integral indices; in configuration-interaction (CI) and transition property calculations, angular integrals are not stored and an ordered list of radial integrals is searched and augmented as required as the calculation progresses; in MC and CI calculations, the lower triangle of the Hamiltonian matrix is stored in a sparse representation; the Davidson–Liu algorithm [E.R. Davidson, J. Comput. Phys. 17 (1975) 87; Comput. Phys. Comm. 53 (1989) 49; B. Liu, in: C. Moler, I. Shavitt (Eds.), Numerical Algorithms in Chemistry: Algebraic Methods, Lawrence Berkeley Laboratory, Berkeley, California, 1978; C.W. Murray, S.C. Racine, E.R. Davidson, J. Comput. Phys. 103 (1992) 382. [1]] as implemented by Stathopoulos and Fischer [A. Stathopoulos, C. Froese Fischer, Comput. Phys. Comm. 79 (1994) 1. [2]] is used to extract the eigenvalues and eigenvectors of interest. Certain linear-algebraic operations are preformed using subprograms from the BLAS [C.L. Lawson, R.J. Hanson, D. Kincaid, F.T. Krogh, ACM Trans. Math. Soft. 5 (1979) 308; J. Dongarra, ACM Trans. Math. Soft. 14 (1988) 1; J.J. Dongarra, J. Du Croz, S. Hammarling, R.J. Hanson, ACM Trans. Math. Soft. 14 (1988) 18; J.J. Dongarra, J. Du Croz, I.S. Duff, S. Hammarling, ACM Trans. Math. Soft. 16 (1990) 1, 18. [3]] and LAPACK [E. Anderson, Z. Bai, C. Bischof, J. Demmel, J. Dongarra, J. Du Croz, A. Greenbaum, S. Hammarling, A. McKenney, S. Ostrouchov, D. Sorensen, LAPACK User's Guide, Society for Industrial and Applied Mathematics, Philadelphia, 1992. [4]] libraries. Angular-momentum recoupling coefficients are computed using the NJGRAF package of Bar-Shalom and Klapisch [A. Bar-Shalom, M. Klapisch, Comput. Phys. Comm. 50 (1988) 375. [5]]. A minor revision of a preprocessor program due to K.G. Dyall [K.G. Dyall, Comput. Phys. Comm. 39 (2986) 141. [6]] is used to automate the setting of array dimensions and the selection of installation-dependent features. Running time: CPU time required to execute test cases: 300 min